Pelvimetric profiles in crossbred cows of Andaman and Nicobar Islands - PERUMAL, P; DE, A K; BHATTACHARYA, D; MUNISWAMY, K; SUNDER, J; KUNDU, A; AHMAD, S K ZAMIR (The Indian Journal of Animal Sciences, 2019)
A study was conducted in crossbred cows maintained atorganised dairy farm of the institute to select cows based on the external pelvimetric measurements associated with body weight for breeding purpose. Cows (32) selected were divided in to 4 groups based on age, viz. Gr I (24–36 months), Gr II (37–48 months), Gr III (49–53 months), Gr IV (>53 months) with 8 cows in each group. Overall mean area of pelvic inlet and outlet was 235.61±4.74 and 147.90±5.21 cm2, respectively. The study concluded that pelvimetric parameters and body weight were significantly higher in Gr IV than other younger animals (Gr I, II and III). These pelvimetric parameters and body weight increased as age advanced and differed significantly between the age groups. The body weight was positively correlated with pelvic area (r=0.92) and age (r=0.88). These findings will be helpful in selection of crossbred cows for breeding purpose in Andaman and Nicobar Islands.